An Ultra-Wideband Absorber Backed Planar Slot Antenna - William O. Coburn , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Planar antenna designs have many advantages such as low-profile, light-weight, and ease of fabrication and integration. Here, a planar slot antenna implemented on ceramic substrate with coplanar waveguide feed is considered. With absorber loading the design provides 50 omega input impedance over the frequency range 0.3–3 GHz so it is considered ultra-wideband. This paper summarizes a numerical investigation using both frequency and timedomain solvers. The results serve to guide the future analysis of broadband antennas with lossy dielectric loading for ground penetrating radars. The evaluation of radar performance requires further simulation and model validation based on antenna measurements.